A Ciranda Infantil e as crianças sem terrinha educação e vida em movimento - Barcellos, Luís Henrique dos Santos (Editora Oficina Universitária, 2021)
In such an emblematic moment of attacks on democracy, social and worker rights, this book presents itself as a cry for existence and resistance. Existence of multiple and different conditions and ways of being, of acting and thinking, of producing human life, transformed daily in the historical movement. A cry for the existence of multiple and different childhoods, in particular, childhood lived in the countryside and within a social movement such as the MST. A cry of resistance to the chaotic Brazilian situation permeated by a harsh crisis that, before the current health crisis, is also political, social and economic. There are many and important examples of cries for existence and resistance present in the struggle of the Landless and Landless of the MST. From the first struggle for land (agrarian reform), to the struggle for school, health, funding and all that are necessary for the establishment of dignified human life conditions. In the midst of this turmoil, Ciranda Infantil and Sem Terras are seeds of hope.